Optimization of microwave assisted enzymatic extraction of steviol glycosides and phenolic compounds from Stevia leaf - Görgüç, Ahmet; Gençdağ, Esra; Yılmaz, Fatih (Acta Periodica Technologica, 2019)
Stevia (Stevia rebaudiana Bertoni) has gained great interests due to its non-caloric and health related properties with its steviol glycosides and phytochemical constituents. Currently, it is being utilized as a natural sweetener in many food formulations such as soft drinks, jams, dairy products, chocolates, etc. Green extraction techniques using non-hazardous solvents and yield-enhancing strategies have been subject matters of various disciplines such as food technology, chemistry and pharmacology. Stevia powders are industrially produced by aqueous-extraction with further purification and drying steps. There has been no any report handling combined microwave and enzyme assisted technique on the extraction of steviol glycosides and antioxidant compounds to date. The objective of this study was to determine optimum processing parameters of microwave assisted enzymatic extraction of steviol glycosides and phenolic compounds by investigating the effects of independent variables. The plant was collected from a stevia garden and its leaves were detached from flower part, dried and milled into powder form before commencement of the treatments. Operations were performed using a microwave extraction system equipped with a digital control system for irradiation time, temperature and microwave power. Viscozyme L which is a widely used cellulolytic enzyme cocktail was used in this study. The effects of enzyme concentration (1.2 - 60 FBG unit g-1), temperature (25-60?C) and time (1 - 20 min) were evaluated using a five-level rotatable central composite design by response surface methodology (RSM). The validities of models were assessed by ANOVA outputs which were determination coefficient (R2), lack of fit and Fisher's test value (F-value). The maximized yields of stevioside, rebaudioside A and total phenolic compounds were determined as 62.5, 25.6 and 20.7 mg g-1, respectively at optimum processing conditions which were estimated as 10.9 FBG unit g-1, 53?C and 16 min. nema